Trends in ecology & evolution (Elsevier Publishers, B.V., 1986)
" ... contains polished, concise and readable reviews, opinions and letters in all areas of ecology and evolutionary science. It serves as an invaluable source of information for researchers, lecturers, teachers, field workers and students. Trends in ecology & evolution keeps these scientists informed of new developments and ideas across the full range of ecology and evolutionary biology - from the pure to the applied, and from molecular to global."